Increasing attendance in a cervical cancer screening programme by personal invitation: experience of a Lithuanian primary health care centre - Kurtinaitienė, Rūta; Rimienė, Jolita; Labanauskaitė, Ingrida; Lipunova, Nadežda; Smailytė, Giedrė (Acta medica Lituanica, 2016)
Background. High participation rates are an essential component of an effective screening programme and many approaches were introduced as being successful for enhancing compliance to screening guidelines. The aim of this study was to evaluate to which extent a personal invitation by mail increases the rate of attendance in a cervical cancer screening programme in a primary health care centre. Materials and methods. The study was carried out as a pilot project to gain insight into feasibility of applying a well-known compliance increasing measure in Lithuanian population. The  study included a  sample of women registered at the  primary health care centre in Panevėžys who had not participated in the cervical cancer screening programme for six and more years. Personal registered invitation letters to attend the primary health care centre for a  Pap smear were sent out to 1789 women by mail. Results. In total, 2195 women were tested during 2011 at the primary health care centre. 487 (22.2%) of them attended the screening programme after receiving a personal invitation letter. Response rate for attending screening after receiving a personal invitation letter was 27.3%. Conclusions. Our study demonstrated that personal invitation letters addressed to long-term non-attendees could markedly increase participation in cervical cancer screening in Lithuania.
Keywords: Pap smear; cervical cancer screening; attendance